Pengaruh Kompetensi, Motivasi, dan Kompensasi terhadap Kinerja Aparatur Pemerintah Desa dalam Pemgelolaan Keuangan di Kabupaten Pelalawan - Rendy Andryan; Halkadri Fitra (Jurnal Eksplorasi Akuntansi, 2026)
This study aims to obtain empirical evidence regarding the influence of competence, motivation, and compensation on the performance of village government officials in financial management in Pelalawan Regency. A total of 184 respondents from 104 villages participated in this quantitative survey using purposive sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that competence, motivation, and compensation significantly influence the performance of village government officials. These findings support the stewardship theory framework and provide practical insights for improving financial management at the village level. This study is limited to village officials in the mainland area of Pelalawan District with an IDM category of “advanced,” so it does not represent all village conditions. Additionally, only three variables were examined. Further research is recommended to cover a broader area, include additional variables, and use qualitative methods such as interviews for more in-depth results.